Diseases of the Salivary Glands—Part II - Sisto, Margherita (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The year 2021 saw the publication of the Special Issue ""Diseases of the Salivary Glands" (https://www.mdpi.com/journal/jcm/special_issues/Salivary_Glands), Part I, covering recent and novel advancements as well as future trends in the field of research evaluating diagnostic and therapeutic treatment of salivary gland (SGs) diseases. Given the enormous success of Part I, the Special Issue "Diseases of the Salivary Glands" Part II has been launched, with the firm belief that it will enrich the panorama of world research in this field. Topics include: 1) Clinical features and presentation of potentially malignant SG disorders; 2) Risk factors and etiopathogenesis of SGs tumors; 3) Etiopathogenesis and molecular mechanisms involved in the chronic inflammatory condition characterizing Sjӧgren's syndrome; 4) New discoveries in the field of micro RNAs associated with Sjӧgren's syndrome; 5) Molecular markers linked to development and progression of SG diseases: current knowledge and future implications; 6) More innovative techniques for the study of the SG diseases: current limitations and future directions.